A to Z of criminal trial under criminal laws w.e.f. 1-7-2024 - Singh, Pramod Kumar (New Delhi Commercial Law Publishers, 2025)
A to Z of Criminal Trial Under Criminal Laws w.e.f. 1-7-2024 Exhaustive Comments & Case Laws Model Forms of Pleadings and Draftings Words & Phrases Table showing Classification of Offences Practice & Procedure involved in Criminal Trial Law on Every aspect and stages of Criminal Trial Practical Tips on Successful defences in Criminal Trial Corparative Table of Cr. P.C. with BNSS
Keywords: Criminal Law; Criminal Trial